2009
DOI: 10.1590/s0037-86822009000600001
|View full text |Cite
|
Sign up to set email alerts
|

Entomological surveillance of Chagas disease in Berilo municipality, Jequitinhonha Valley, State of Minas Gerais, Brazil

Abstract: This study aimed to evaluate the Chagas Disease Control Program which has operated since 1982 in the municipality of Berilo in the Jequitinhonha Valley, Minas Gerais, Brazil, based on evaluation of 5,242 domiciliary units (DUs) and 7,807 outbuildings over an eight-year period of epidemiological surveillance implanted in 1997. A total of 391 triatomines (280 Panstrongylus megistus and 111 Triatoma pseudomaculata) were captured, indicating the continued predominance of the former species. However, Triatoma pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.Regardless of the fact that it has remained the most collected species in cerrado areas of Brazil for the past years 18,45-47 , T. sordida presents a low risk of transmission of T. cruzi to humans because of its peridomiciliary behavior and marked ornithophily 15,34,[46][47] . Some studies show that zones of higher occurrence of T. sordida correspond to those of higher and older farm exploration 33 , which may justify the higher frequency of this species in Planaltina.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…This fact may be associated to environmental (deforestation, urban expansion) and social (migration, electrifi cation of rural domiciles) changes that occurred in the area, as observed for T. pseudomaculata in a municipality of this region, where the presence of the species seems to be related to the changes in primary land coverage and aridifi cation (14) .…”
mentioning
confidence: 74%